THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND AMBASSADOR ON PURCHASE INTENTION FOR RUCAS (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the influence of social media marketing and brand ambassadors on purchase intention for Rucas products. The rapid growth of social media as a primary marketing tool has encouraged many companies to utilize robust digital marketing strategies and strategic brand ambassador partnerships to effectively increase consumer purchase intention. This study employed a quantitative method with a descriptive approach to analyze these variables. The sampling technique utilized non-probability sampling with a specific purposive sampling method. Data were obtained by distributing online questionnaires to targeted respondents who either knew or actively followed Rucas' official social media accounts. Data analysis was performed using multiple linear regression analysis to rigorously test the influence of social media marketing and brand ambassadors on purchase intention. The results demonstrate that social media marketing has a positive and significant effect on purchase intention for Rucas products. Furthermore, brand ambassadors also exert a positive and significant effect on the purchase intention for Rucas products. Simultaneously, social media marketing and brand ambassadors significantly influence consumer purchase intention for Rucas products. These comprehensive findings suggest that an effective social media marketing strategy, combined with the appropriate selection and use of brand ambassadors, can substantially increase consumer purchase intention for Rucas products in the competitive modern market